THE SEX SYSTEM OF THE POPULATION OF SAGITTARIA SAITTIFOLIA AS AN INDICATOR OF THE ECOLOGICAL STATUS OF A RIVER (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The ecological state of small rivers that define the water regime of the territory, as well as the water supply of larger rivers, the quality of their waters is a matter of a serious concern. The ecosystems of watercourses in urban areas exposed to pollution by industrial and domestic wastes are under the maximum anthropogenic load. Bioindicative methods, which let to assess directly the status of aquatic ecosystems and their individual components, occupy an important place in the system of ecological monitoring of water bodies. Plants respond to toxicants in an aquatic habitat by the abnormality of biosynthesis of chlorophyll, carotenoids and other pigments, change of mineral balance, phytohormones, which leads to a change in their reproductive differentiation.In this regard, water quality assessment was carried out on the basis of chemical analysis and bioindication concerning Sagittaria sagittifolia populations in the upper and middle stream ways of the river Tyosha flowing through the Nizhny Novgorod region.The article presents the results of some organoleptic and chemical parameters such as pH level of overall hardness, concentration of nitrates and nitrites, ions of ammonium, phosphates, mercury, concentration of oxygen and carbon dioxide in the water. It was detected that there were exceeding quantities of ammonium ions, nitrite ions, phosphates in the water of all ranges of the river Tyosha, and also high content of iron in the downstreams of the river. The findings suggest that the reproductive structure of arrowhead inflorescences can serve as a bio-indicator of the degree of water pollution. The harder the environmental conditions of the plant habitat in the water body, the more intensive is a shift in the ratio of flowers to the feminine side. It has been shown that due to the deterioration of environmental conditions, the number of compound inflorescences of the arrowhead and the numbers of whorls in them decrease and, on the other hand, there is an increase in the percentage of plants with simple typical inflorescences. A credible shift in the reproductive ratio of arrowhead inflorescences to the female side is spotted on the downstream river station near Lukoyanov and industrial community Shatky, where the complex of environmental factors for its growth is the least favorable. It was established that anthropogenic pollution of the river has a negative effect on the reproductive sphere of Sagittaria sagittifolia, causing a reduction in pollen fertility, which is confirmed by the chemical analysis of water.On the basis of the studies the assessment of the ecological status of the water in the Tyosha river was given.